Marvel-verse. Black Panther. - Parker, Jeff, 1966-; Hannigan, Edward; Gillis, Peter B.; Macchio, Ralph; Okorafor, Nnedi (Marvel Worldwide, Inc, 2019)
Collects comic book stories about Marvel's superhero the Black Panther, collecting some of his most important adventures and stories--from the first time the Fantastic Four discover T'Challa's home of Wakanda in the African jungle to when T'Challa is called away with the Avengers and gets lost in space, leaving his sister Shuri to take up the mantle of the Panther.